Economic and Legal Aspects of Regulating the Tourism Industry - DMITRIEVA, Olga Vladimirovna; ISAEVA, Olga Gennadievna; KUBLASHVILI, Oxana Vyacheslavovna; FROLOVA, Victoria Borisovna; KONOVALOVA, Alla Borisovna (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The article deals with the economic and legal aspects of regulating the tourism industry. It is established that a strategy of profitable and effective activities should be carried out at the level of the travel agency, while the policy, which would include methods of planning and coordination of the entire travel industry, should be performed at the level of the individual region. It is proved that the regional community should be involved in tourism development. The authors reveal that the specificity of tourist services is related to the features of tourist demand, which is not uniform because of the impalpability and nonpreservation of the tourist product. This makes it difficult for managers of a travel company to convince each consumer about the feasibility of purchasing a travel service. It is determined that despite the tourism industry is regulated legally, however, its constituent sources often come into conflict with each other, creating legal conflicts, whose solution is unfairly ignored by the legislative bodies.